Dietary and Nutrition Recommendations in Pediatric Primary Care: A Call to Action. Issue 1 (January 2018) - Harrison, Sayward E.; Greenhouse, Deborah
Abstract : Abstract: Rapid increases in childhood obesity reflect widespread changes in diet and physical activity, which are of significant concern because obesity increases a child's risk for negative health outcomes and frequently creates a pathway to adult obesity. Diet and nutrition play a key role in maintaining energy balance and preventing weight gain; therefore, they are obvious targets for obesity prevention efforts. Primary care providers are in an optimal position to convey messages about healthy eating to children and families, and specific guidelines exist for how to incorporate diet and nutrition prevention into primary care. Providers should be aware of the scientific evidence supporting these preventive practices. This review provides a summary of recommendations for integrating diet and nutrition into pediatric primary care and presents a call to action to make diet/nutrition assessment, counseling, and intervention routine aspects of the preventive care visit. Abstract : Counseling and interventions targeting diet and nutrition are key components of childhood obesity prevention, and clear guidelines exist for incorporating these practices into pediatric primary care. This review presents a call to action for primary care providers to devote increased attention to incorporating diet and nutrition into their practice and reviews evidence and guidelines on the integration of diet/nutrition counseling into pediatric primary care.